2002
DOI: 10.1145/568727.568728
|View full text |Cite
|
Sign up to set email alerts
|

Improving retrieval feedback with multiple term-ranking function combination

Abstract: and VITTORIO GIANNINI WIND Telecomunicazioni S.p.A ________________________________________________________________________In this paper we consider methods for automatic query expansion from top retrieved documents (i.e., retrieval feedback) which make use of various functions for scoring expansion terms within Rocchio's classical reweighting scheme. An analytical comparison shows that the retrieval performance of methods based on distinct term-scoring functions is comparable on the whole query set but consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…Using a combined recall/precision measure, the overwhelming majority of recent experimental studies agree that AQE results in better retrieval effectiveness, with improvements of the order of 10% and larger (e.g., [Mitra et al 1998], [Carpineto et al 2002], [Liu et al 2004], ). Such findings are important to support the claim that AQE is an effective technique, but this may be not sufficient for the cases when we are primarily interested in precision.…”
Section: Why and When Aqe Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a combined recall/precision measure, the overwhelming majority of recent experimental studies agree that AQE results in better retrieval effectiveness, with improvements of the order of 10% and larger (e.g., [Mitra et al 1998], [Carpineto et al 2002], [Liu et al 2004], ). Such findings are important to support the claim that AQE is an effective technique, but this may be not sufficient for the cases when we are primarily interested in precision.…”
Section: Why and When Aqe Workmentioning
confidence: 99%
“…In particular, it has been shown that the ordered sets of expansion terms suggested for each query by the different functions are largely uncorrelated [Carpineto et al 2002]. However, several experiments suggest that the choice of the ranking function does not have a great impact on the overall system performance as long as it is used just to determine a set of terms to be used in the expanded query ( [Salton and Buckley 1990], [Harman 1992], ).…”
mentioning
confidence: 99%
“…As there is no clustering algorithm that is intrinsically better or more valid than the others, provided that the structure of the data set is not incompatible with the model of the algorithm [Estivill-Castro 2002], it may be convenient to combine the existing algorithms. Method combination works well for classification [Kittler et al 1998] and query expansion [Carpineto et al 2002], and there is evidence that this is also the case for clustering. Fred and Jain [2005] have shown that merging the results of multiple clustering helps identify clusters with non predefined shapes or structures.…”
Section: Future Trendsmentioning
confidence: 99%
“…Clearly, the standard inverted index which only supports exact matching cannot deal with these cases. Various approaches combining different types of data and se- Code R (1977): This CBS adventure series managed to combine elements of "Adam-12", "Emergency" and "Baywatch" at the same time... O 3 Sound of Music, The (1965): Maria had longed to be a nun since she was a young girl, yet when she became old enough discovered that it wasn't at all what she thought... · · · · · · mantic knowledge have been propose to enhance query processing (cf. Related Works).…”
Section: Introductionmentioning
confidence: 99%
“…Our work can be seen as another alternative to consider the semantic gap by enclosing semantic knowledge directly into an inverted index, so that main tasks can be done before query processing, -User involvement: Most existing works introduce some predefined parameters (heuristics) to rewrite queries such that users are only involved in the query refinement (expansion, filtering, etc.) process after providing the first round of results [3,4,14,20]. In our work, we aim at allowing end-users to write, using the same framework, classical queries but also semantically enriched queries according to their needs.…”
Section: Introductionmentioning
confidence: 99%